The perception of hijabis of integrated marketing communication (IMC) campaigns by dUCk Scarves & Naelofar Hijab: an Aida model perspective - Mohd Tajuddin, Jaslina (Institut Penyiaran dan Penerangan Tun Abdul Razak (IPPTAR), 2023)
Halal has evolved into a way of life with numerous dimensions. The Halal economy has grown beyond the food and beverage industry and has spread out to include other sectors like healthcare, cosmetics, pharmaceuticals, tourism, fashion, and logistics. This current study aims to investigate how integrated marketing communication (IMC) campaigns are used to promote fashion specifically hijab by using the AIDA model. Two successful corporations were selected for this study: dUCk Scarves and Naelofar Hijab. These two businesses were selected due to their existing social standing and significant influence among Muslim women in Malaysia. Qualitative research was selected as the methodology. In-depth interviews with open-ended questions were used to answer the research objectives. Interviews were conducted with 10 hijabis in Malaysia from different age ranges and occupations to understand their perceptions of the hijab brands that used IMC campaigns, framed by the AIDA model. Findings show that IMC campaigns do influence consumer attention, interest, desire, and action. Besides, new elements of the AIDA model are discovered from this research study.